1990
DOI: 10.21273/hortsci.25.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Effects of Weeds on the Growth of Container-grown Plants

Abstract: A 2-year study evaluated the effects of three weed species: eclipta [Eclipta alba (L.) Hasskarl], prostrate spurge (Euphorbia supina Raf.), and wood sorrel (Oxalis stricta L.) on growth of container-grown `Gumpo White Sport' azalea (Rhododendron eriocarpum), R. x `Fashion', and Berberis thunbergii DC. var. atropurpurea `Crimson Pigmy'. Competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 0 publications
0
45
0
2
Order By: Relevance
“…This negative effect on the growth of the cultivated plants can be the result of competition with weed plants for resources (light, water, and nutrients), but also of the release by weeds of root growth-inhibiting chemicals [4]. The latter is generally called allelopathy [29] and has been reported to be stronger in containers [4]. Another possible contribution to this negative effect can be due to the possible phytotoxicity of the herbicide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This negative effect on the growth of the cultivated plants can be the result of competition with weed plants for resources (light, water, and nutrients), but also of the release by weeds of root growth-inhibiting chemicals [4]. The latter is generally called allelopathy [29] and has been reported to be stronger in containers [4]. Another possible contribution to this negative effect can be due to the possible phytotoxicity of the herbicide.…”
Section: Resultsmentioning
confidence: 99%
“…In container cultivation, most of these negative effects may be amplified compared to open-field cultivations because of the reduced availability of growing media. Furthermore, the high fertility of the growth substrate often enhances weed growth rate compared to open-field cultivations [4]. Padgett and Frazier [5] estimated that manual weed control in nursery container cultivation requires 1542 h of labor per hectare.…”
Section: Introductionmentioning
confidence: 99%
“…Fretz (1972) demonstrated that one large redroot pigweed (Amaranthus retroflexus L.) or large crabgrass (Digitaria sanguinalis L.) reduced the growth of 'Convexa' Japanese holly (Ilex crenata 'Convexa') by 47% and 60%, respectively. Similarly, Berchielli-Robertson et al (1990) reported a 43% reduction in Fashion azalea (Rhododendron · 'Fashion') from one eclipta (Eclipta prostrata L.) plant. Other studies have also reported similar growth reductions from a wide variety of weed species on many different ornamental crops (Norcini and Stamps, 1994;Walker and Williams, 1989).…”
Section: Introduction To Current Weed Control Methodsmentioning
confidence: 96%
“…Nursery crop producers growing containerized ornamentals face several unique challenges pertaining to weed management. First, as container-grown plants are produced in a restricted rooting environment, it only takes one weed to negatively impact crop growth and marketability (Berchielli-Robertson et al, 1990;Fretz, 1972;Walker and Williams, 1989). Fretz (1972) demonstrated that one large redroot pigweed (Amaranthus retroflexus L.) or large crabgrass (Digitaria sanguinalis L.) reduced the growth of 'Convexa' Japanese holly (Ilex crenata 'Convexa') by 47% and 60%, respectively.…”
Section: Introduction To Current Weed Control Methodsmentioning
confidence: 99%
“…Survival and growth of transplants were assessed at regular intervals over the next 7 years. For each plant, the height ( H ), together with the maximum and its orthogonal widths (W1, W2) were measured, and growth indices were calculated as ( H + W1 + W2)/3 (Berchielli-Robertson et al . 1990).…”
Section: P R O S T a N T H E R A E U R Y B I O I D E Smentioning
confidence: 99%